Diagnostic utility of PRAME expression by immunohistochemistry in subungual and non‐subungual acral melanocytic lesions. (25th July 2022) - Rothrock, Aimi T.; Torres‐Cabala, Carlos A.; Milton, Denái R.; Cho, Woo Cheal; Nagarajan, Priyadharsini; Vanderbeck, Kaitlin; Curry, Jonathan L.; Ivan, Doina; Prieto, Victor G.; Aung, Phyu P.
Abstract: Background: The immunohistochemical (IHC) marker PReferentially expressed Antigen in MElanoma (PRAME) has shown promise in the diagnosis of melanocytic lesions. A few studies have investigated PRAME IHC expression in acral melanomas, but PRAME expression in subungual melanomas is largely unknown. We evaluated the utility of PRAME IHC expression in distinguishing subungual melanomas (SUM) and non‐subungual acral melanomas (AM) from acral nevi (AN). Methods: Twenty‐two SUM, 20 AM, and 14 AN were identified. IHC studies were performed using an anti‐PRAME antibody. The percentage of lesional cells with PRAME expression was recorded and categorized as follows: 0%, 0; 1%–25%, 1+; 26%–50%, 2+; 51%–75%, 3+; and >75%, 4+. Patient demographics and other relevant clinicopathologic parameters were recorded. Results: Diffuse (4+) PRAME IHC expression was identified in 55% (12/22) SUM and 70% (14/20) AM, respectively. Any PRAME expression (1+ to 4+) was identified in 73% (16/22) SUMs and 95% (19/20) AM, respectively. One of 14 (7%) AN exhibited PRAME expression; interestingly, the pattern of expression was diffuse. Conclusions: In our study, PRAME IHC expression was useful in identifying AM, including SUM. However, there are exceptions of PRAME‐negative melanomas and PRAME‐positive nevi.